National Food, Nutrition and Physical Activity Survey of the Portuguese general population - Lopes, Carla (2017)
The National Food, Nutrition and Physical Activity Survey of the Portuguese general population aimed to collect nationwide and regional data on dietary intake and physical activity, and their relation with health determinants, namely socioeconomic factors. Results from this project were obtained from a representative sample of the Portuguese population, aged between three months to 84 years of age, selected from the National Heath Registry, by multistage sampling (a sample size of 5068 individuals was estimated and 5811 participants with two dietary assessments were achieved). To accomplish the EFSA requirements, a minimum, of 260 individuals in each age group (130 by sex) was planned. Two face-to-face interviews were conducted at a health care centre or participant’s home. Dietary intake was obtained by two non-consecutive days of food diaries for children (<10 years old) and two non-consecutive 24-hours recalls for the older age groups, with a time interval between 8 and 15 days, complemented with a Food Propensity Questionnaire. An electronic platform based on a client-server architecture was used to manage the field work and to assist the data collection. The Electronic Assessment Tool for 24-hours recall (eAT24) allowed the collection of dietary data by an Automated Multiple-Pass Method for 24-hours. This interview-based dietary assessment instrument allowed obtaining a very detailed description and quantification of foods, recipes, and food supplements consumed in the course of the preceding day, and it had several adaptations, described in detail in this report. The survey outcomes support solid evidence-based information covering all age groups of the population, using harmonized methodologies at the European level, and will contribute to develop a national infrastructure for monitoring progress of specific targets supporting national and European policies and future interventions on diet, physical activity and food safety.